Self-perception of teaching performance in distance education: evidence from the course Matemática Nivelatoria at UNED - Barrantes - Gutiérrez, Jeffry (2025)
This descriptive-evaluative study employed an expert-validated mixed self-evaluation questionnaire sent to seven UNED tutors in the bridging Mathematics course; only three responded. Findings reveal uneven mastery of the institutional model, reliance on extrinsic motivators, fragmented self-regulation scaffolds and mainly corrective, delayed feedback—a combination linked to dropout and irregular achievement. The paper recommends a practice-oriented development programme, integrated self-regulation scaffolding, a continuous multimodal feedback system and strategies that cultivate intrinsic motivation, all to be monitored longitudinally to assess impact.